Helminthological Examination of a Sheep Infected with Dictyocaulus filaria - Sharipovna, Sharipova Laylo; Ergashovich, Yuldashev Nurbek (American Journal of Biology and Natural Sciences, 2026)
Dictyocaulosis is a significant parasitic disease of domestic ruminants caused by Dictyocaulus filaria, which inhabits the respiratory tract and leads to respiratory disorders, reduced productivity, and economic losses. This study aimed to confirm and characterize ovine dictyocaulosis using larvoscopic and pathological diagnostic methods. In March 2026, a sheep suspected of dictyocaulosis was examined at the Helminthology Laboratory of the Veterinary Research Institute. Fecal samples were analyzed using the Baermann–Orlov–UzVRI larvoscopic method, which detected Dictyocaulus larvae. Necropsy was performed according to K. I. Skryabin’s partial dissection method. Macroscopic examination revealed numerous milky-white adult nematodes in the bronchi, accompanied by foamy mucous exudate, catarrhal inflammation, and excessive mucus accumulation in the lungs. The recovered helminths were preserved in 70% ethanol and identified as Dictyocaulus filaria based on their morphological characteristics. Male worms measured 4.8–7.2 cm, while females measured 6.5–8.7 cm. Larvated eggs in the female uterus measured 0.112–0.138 × 0.069–0.090 mm. These findings confirmed D. filaria infection and demonstrated that combining larvoscopic, pathological, and morphological examinations provides reliable diagnosis. Regular strategic deworming and effective anthelmintic treatment are essential for disease prevention and control.